2003
DOI: 10.1590/s0004-27492003000700007
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between optical coherence tomography and fundus fluorescein angiography in post-cataract surgery cystoid macular edema

Abstract: Agreement between optical coherence tomography and fundus fluorescein angiography in post-cataract surgery cystoid macular edema Purpose: To evaluate the agreement between optical coherence tomography (OCT) and fundus fluorescein angiography (FFA) regarding the detection of cystoid macular edema (CME) following cataract surgery. Methods: Retrospective comparative observational series of 25 eyes with suspected CME. Patients with low visual acuity and alterations in fundus biomicroscopy after cataract surgery un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…FFA was compared with OCT by Mitne et al for the diagnosis of CME, who found an 88% correlation between the two methods [14]. The same comparison was performed by Antcliff et al who reported that the sensitivity and specificity of OCT was 96% and 100%, respectively [15].…”
Section: Discussionmentioning
confidence: 99%
“…FFA was compared with OCT by Mitne et al for the diagnosis of CME, who found an 88% correlation between the two methods [14]. The same comparison was performed by Antcliff et al who reported that the sensitivity and specificity of OCT was 96% and 100%, respectively [15].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Historically, fundus fluorescein angiography (FFA) was widely regarded as the standardized method for detecting CME. 5 Introducing advanced technology, such as optical coherence tomography (OCT), has provided a rapid and non-invasive means of detecting CME and other retinal conditions with significantly reduced side effects. 6 Many ocular and systemic conditions are noted to increase the risk of PCME, one of the major co-morbidities being diabetes.…”
Section: Introductionmentioning
confidence: 99%